Improving the Eleventh Graders' Recount Text Writing through Mind mapping Technique at SMA PSKD 7 Depok - Alam, Angga Putra (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2017)
AbstractThe objective of this research was to improve the eleventh graders’ recount text writing skill. To attain the objective a two-cycled classroom action research was conducted in SMA PSKD 7 Depok. The 28 students of the eleventh graders who participated in this research were taught recount text through mind mapping technique. The quantitative data, collected using tests, were analyzed by using statistical analysis technique. The qualitative data, collected using observation sheets and interview guide, were analyzed by using descriptive analysis technique. The results indicated that the mind mapping technique improved the eleventh graders’ recount text writing skill, as shown by the increase of the mean scores of the tests conducted, i.e. 52,61 (in the pretest) to 70.61 ( post-test of cycle 1) to 80.29 (post-test of cycle 2). Based on the findings, it could be concluded that through implementation of mind mapping technique, students’ recount text writing skill could improve. Keywords: Mind mapping technique, writing skill, classroom action research